The Balance Of The Money And Goods Markets From An Islamic Economic Perspective - Febrian Maulana Putra; Syamsul Hilal; Hanif Hanif (Jurnal Pajak dan Analisis Ekonomi Syariah, 2025)
This study aims to determine the balance of the money and goods markets from an Islamic economic perspective. The research method used is the study of literature from articles, papers, books, and other sources that support the problem under study. The results of this study indicate that Islamic economics states that when prices are fixed, income and interest, or the expected rate of profit, are at a level that balances the commodity market and the money market. The equilibrium level of income and welfare is at the intersection of the IS and LM curves, using the interest rate and the expected rate of return. In Islamic economics, a similar mechanism occurs in the economy that income and the anticipated rate of return lead to the equilibrium level. However, as previously mentioned, changes in income do not directly cause changes in the money market interest rate, which creates a balance between the demand for money and the money supply. Therefore, the interest rate on the interest income panel can only be determined by the IS curve without the LM curve. In other words, the interest rate always appears on the IS curve but can also occur outside the LM curve.